Lease and finance evaluation : applications for successful financing alternatives - Day, Alastair L.; Euromoney Publications PLC (London : Euromoney, 1996)
Aimed at finance directors, clients and buyers of finance who want to evaluate leasing and finance quotations properly and compare the costs against other forms of finance or the cost of capital; and leasing company and banking executives who prepare and structure quotations or wish to provide information about various finance options for their clients.
"User manual V2.0 31 March 1996" - T.p.
&#x000A
Includes bibliographical references.
oif 08/04/15
Loan
Keywords: Finance -- Management -- Use of -- Computers; Electronic spreadsheets -- Computer programs; Lease and rental services -- Finance; Decision support systems; Business enterprises -- Finance